Stimulating Effect of Ozone Low Doses on Microorganisms’ Growth - Belykh, I. A.; Zinchenko, V. D.; Vysekantsev, I. P. (Problems of Cryobiology and Cryomedicine, 2004)
Ozone in dosed amount was added to growth medium of Esherichia coli bacteria or Candida albicans yeast-like fungi and the kinetics of microorganism growth depending on its amount was under observation. With the ozone dose of 0.3-0.5 mg/l in growth medium there was found the growth stimulation of microorganisms, with higher doses the growth suppression was found. If Candida albicans fungi are subjected to freezing down to –196°C and then to thawing, then with adding ozone to growth medium before freezing more intensive fungi growth after thawing is noted.